(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Behavior analysis is regularly labeled as a natural science but the rationale for this classification is seldom presented. In order to discuss criteria and implications of assigning this label to the behavior analysis, behavior analysts’ texts that defended this classification were analyzed. It was found that the criteria were not clear enough to justify this labeling to the detriment of others and that possible undesirable implications were ignored. Lastly, the understanding of behavior analysis as a science beyond the natural science label may help dissolving misunderstandings, demonstrating the diversity of behavior-analytical investigations, and propitiating its dialogues with other disciplines.